Pengaruh Fee Audit dan Audit Tenure terhadap Kualitas Audit - Yulaeli, Tri (Jurnal Buana Akuntansi, 2022)
Abstract This study aims to examine the effect of audit fees and audit tenure on audit quality. This study uses a quantitative approach with a sample of manufacturing companies in the sub-sector of various industries as well as companies in the property, housing and building construction sectors that have been listed on the BEI, which are 129 companies. This research uses a purposive sampling technique, with the help of the SPSS application statistical tools in managing the results and also hypotheses. The results of the study indicate that the audit fee has a positive and significant effect on audit quality. Meanwhile, audit tenure has no significant effect on audit quality. The results of this study support the signaling theory, namely a high audit fee can be a positive signal that the public auditor has sufficient experience and ability and is able to produce high audit quality. This research can contribute to the company as a quantitativ empirical evidence related to the effect of audit fees on audit quality, so the company needs to consider the amount of audit fees as a signal of good audit quality and be able to report material misstatements